Accumulation of Gene Polymorphisms Related to Plaque Disruption and Thrombosis Is Associated With Cerebral Infarction in Subjects With Type 2 Diabetes - Katakami, Naoto; Takahara, Mitsuyoshi; Kaneto, Hideaki; Shimizu, Ikki; Ohno, Keizo; Ishibashi, Fukashi; Osonoi, Takeshi; Kashiwagi, Atsunori; Kawamori, Ryuzo; Shimomura, Iichiro; Matsuhisa, Munehide; Yamasaki, Yoshimitsu (Diabetes care, 2010)
OBJECTIVE: It is believed that disruption of vulnerable atherosclerotic plaque and subsequent thrombus formation play critical roles in the pathogenesis of cerebral infarction. We simultaneously determined four relatively common genetic variants related to plaque rupture or subsequent local thrombus formation and evaluated the combined effect on cerebral infarction. RESEARCH DESIGN AND METHODS: We enrolled 3,094 Japanese type 2 diabetic subjects (62.7% male; aged 61.5 ± 8.4 years) and determined their genotypes regarding matrix metalloproteinase 9 C-1562T, coagulation factor XII (F12) C46T, von Willebrand factor (VWF) G-1051A, and plasminogen activator inhibitor (PAI-1) 675 4G/5G polymorphisms. The diagnosis of cerebral infarction was performed based on history, physical examination, and neuroimaging. RESULTS: The single association analysis revealed that there were no statistically significant associations between each polymorphism and the prevalence of cerebral infarction. Interestingly, the prevalence of cerebral infarction was higher with the increase of the total number of four concomitant unfavorable proatherothrombotic alleles in each subject (P value for linear trend = 0.004). Furthermore, a multiple logistic regression analysis showed that the number of proatherothrombotic alleles was a risk factor for cerebral infarction independently of conventional risk factors (odds ratio for one-point increase in the number of proatherothrombotic allele 1.15 [95% CI 1.05-1.26], P = 0.004). CONCLUSIONS: Accumulation of gene polymorphisms related to plaque rupture and thrombus formation is likely associated with the prevalence of cerebral infarction in type 2 diabetic patients, suggesting that the combined information about these variants is useful to assess the risk of cerebral infarction.